2017
DOI: 10.22354/in.v21i4.687
|View full text |Cite
|
Sign up to set email alerts
|

Effects of biocide exposure on P. Aeruginosa, E. coli and A. Baumannii complex isolates from hospital and household environments

Abstract: Background: Bacterial responses to biocide exposure and its effects on survival and persistence remain to be studied in greater detail. Aim: To analyse the viability and survival of environmental isolates from household and hospital settings after biocide exposure. Methods: The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of chlorhexidine (CHxG), benzalkonium chloride (BAC) and triclosan (TC) were determined in isolates of Pseudomonas aeruginosa, Acinetobacter baumannii c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Therefore, it seems that hygiene control of surfaces and medical equipments in the hospital settings in terms of P. aeruginosa contamination is important because nosocomial infections are considered as a growing global threat in terms of economical and public health [3]. The most common antiseptic and disinfectant biocides used in clinical settings are chlorhexidine digluconate (a biguanide, disrupting the cell membrane), benzalkonium chloride (a quaternary ammonium compound, disrupting the cell membrane), triclosan (a bisphenol, blocking of lipid biosynthesis) and formaldehyde (an aldehyde, alkylating agent) [4,5]. However, several studies have reported bacterial resistance to various biocides due to the presence of resistance genes [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it seems that hygiene control of surfaces and medical equipments in the hospital settings in terms of P. aeruginosa contamination is important because nosocomial infections are considered as a growing global threat in terms of economical and public health [3]. The most common antiseptic and disinfectant biocides used in clinical settings are chlorhexidine digluconate (a biguanide, disrupting the cell membrane), benzalkonium chloride (a quaternary ammonium compound, disrupting the cell membrane), triclosan (a bisphenol, blocking of lipid biosynthesis) and formaldehyde (an aldehyde, alkylating agent) [4,5]. However, several studies have reported bacterial resistance to various biocides due to the presence of resistance genes [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies have reported bacterial resistance to various biocides due to the presence of resistance genes [6]. On the other hand, the risk of P. aeruginosa infections in ICU-hospitalized patients is high (up to 30%) despite applying hygiene programs [5]. Such a high prevalence can be attributed to the reduced susceptibility of P. aeruginosa strains against a variety of antiseptics and disinfectants over time [7].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it seems that hygiene control of surfaces and medical equipments in the hospital settings in terms of P. aeruginosa contamination is important because nosocomial infections are considered as a growing global threat in terms of economical and public health [3]. The most common antiseptic and disinfectant biocides used in clinical settings are chlorhexidine digluconate (a biguanide), benzalkonium chloride (a quaternary ammonium compound), triclosan (a bisphenol) and formaldehyde (an aldehyde) [4,5]. However, several studies have reported bacterial resistance to various biocides due to the presence of resistance genes.…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies have reported bacterial resistance to various biocides due to the presence of resistance genes. On the other hand, the risk of P. aeruginosa infections in ICU-hospitalized patients is high (up to 30%) despite applying hygiene programs [5]. Such a high prevalence can be attributed to the resistance of P. aeruginosa strains against a variety of antiseptics and disinfectants over time [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation